2006
DOI: 10.1111/j.1439-0442.2006.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Manifestation of Encephalitozoonosis in Mice after Experimental Infection with Different Species and Application of Dexamethasone

Abstract: Twenty-eight BALB/c mice were infected with different strains of Encephalitozoon species (Encephalitozoon cuniculi II - mouse type, E. cuniculi III - dog type, Encephalitozoon hellem, Encephalitozoon intestinalis). Five of them were infected with E. cuniculi II (mouse type) and simultaneously immunosuppressed with dexamethasone. Clinical signs of encephalitozoonosis were not remarkable. Ascites was found in two mice of dexamethasone-treated group 14 days post-infection (p.i.). The histopathological changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Seroconversion precedes renal shedding and is still detectable afterwards [ 77 ] ( Figure 1 ). Whether or not shedding increases in immunocompromised rabbits is debatable: some authors have not shown any effect of dexamethasone administration on spore excretions [ 39 ] while others suggest the contrary [ 100 ], as dexamethasone has been reported to increase spore excretion in mice [ 101 , 102 ]. Urinary spore excretion typically occurs between four weeks and 12 weeks post-infection [ 77 ], which may be earlier than the development of clinical signs.…”
Section: Rabbit and Rodents Encephalitozoonosismentioning
confidence: 99%
“…Seroconversion precedes renal shedding and is still detectable afterwards [ 77 ] ( Figure 1 ). Whether or not shedding increases in immunocompromised rabbits is debatable: some authors have not shown any effect of dexamethasone administration on spore excretions [ 39 ] while others suggest the contrary [ 100 ], as dexamethasone has been reported to increase spore excretion in mice [ 101 , 102 ]. Urinary spore excretion typically occurs between four weeks and 12 weeks post-infection [ 77 ], which may be earlier than the development of clinical signs.…”
Section: Rabbit and Rodents Encephalitozoonosismentioning
confidence: 99%
“…We recently described increases in zebrafish whole-body cortisol following chronic crowding or acute handling stress (Ramsay et al 2006; Ramsay et al accepted). In other animal models exposure to corticosteroids generally increases the intensity of microsporidiosis (Feng et al 2006; Herich et al 2006; Lovy et al 2008). …”
Section: Introductionmentioning
confidence: 98%
“…In vivo infection of microsporidia to wild-type mice was achieved as follows. 1X10 7 E. hellem spores/mice/day were inoculated into wild-type mice for two days, the mice were transiently pre-treated with dexamethasone (Aladin, Cas 2392-39-4, China) to increase infection rates but no significant effects on immune cells as assessed in our established murine model and other reports (35)(36)(37)(38). The control groups were either treated with PBS, LPS (5mg/kg), or S. aureus (1X10 7 CFU/mice).…”
Section: Microsporidia Infectionmentioning
confidence: 84%